IEEE Thirteenth Symposium on Fusion Engineering
DOI: 10.1109/fusion.1989.102460
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-carbide composite materials for the ARIES-I reactor study

Abstract: Thr ARIES-I tokamak is a conceptual reactor drsigii based on advanced technology and modest extrapolation from the present clay physics database. The ARIES-I blanket ntilizes SiC'/SiC' composite materials as structural material with lieliiini gas as the coolant. Until recently the brittle failure behavior of monolithic ceramic materials has posed a i~rohlem for rising ceramics as structural materials. Recent development s in nia~iiifact uring and processing of fiber-reinforced rerainics make Si<'/Sic' composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The main method used to improve the strength and fracture toughness is through fiber reinforcement. Different methods can be used to infiltrate the Sic into a fibrous Sic preform [7]. Recent advances in Sic composite manufacturing processes have greatly improved the failure mode behavior, strain tolerance, and fracture toughness of these ceramics.…”
Section: Structural Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main method used to improve the strength and fracture toughness is through fiber reinforcement. Different methods can be used to infiltrate the Sic into a fibrous Sic preform [7]. Recent advances in Sic composite manufacturing processes have greatly improved the failure mode behavior, strain tolerance, and fracture toughness of these ceramics.…”
Section: Structural Materialsmentioning
confidence: 99%
“…Using a finite element calculation, the detailed structural design of the first wall was analyzed. It was shown that the maximum local stress can be designed to below the 180 MPa design limit of the Sic composite material [7].…”
Section: First-wall Designmentioning
confidence: 99%
See 1 more Smart Citation